Description of Single Mother's Parenting Pattern on The Development of Adolescent Personality in Maulafa Village - Qharezha Cicilia Lololau; Dian Lestari Anakaka; Noorce Ch. Berek; Apris A Adu (Universitas Nusa Cendana, 2021)
Family is one of the most important parts of society. In the family all come from. All teachings and habits that will be done in the community are learned in the family. Therefore, in order to function properly in the community of course must start from the family. Life in the family is very important and greatly affects a person in interacting. Various problems that occur in the family that interfere with the wholeness and harmony in the family will make the family have problems. One of them is divorce or in the living death that results in a woman having to perform various roles in her family. Starting from taking care of children, providing a good parenting pattern and also replacing her husband's role as a leader and breadwinner in the family are all taken expertly by the mother. The purpose of this study is to find out the pattern of single mother's foster care towards the reflection of adolescent personality in Maulafa Village. This study uses a qualitative approach. Data retrieval techniques using purposive sampling techniques. So the researchers managed to gather 9 participants (3 participants Single Mother, 3 participants Adolescent children from each Single Mother, and 3 Significant orders from each participant).